English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

um.. this is what i did...

0 = (cos x)/(2 + sin x)

(2 + sin x) (0) = cos x

0 = cos x

x = pi/2 and 3pi/2....

um.. i dont know if i did that right..

thanks!

2007-09-26 11:58:20 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

y = cos x / ( 2 + sin x) . . . . use derivative of fraction
y ' = [ cos x ( cosx) - ( 2 + sin x)(- sin x ) ] / ( 2 + sin x)^2 = 0
cos^2 x + 2 sin x + sin^2 x = 0
2 sin x = -1 . . . . . . . . . . . . since . . . sin^2 x + cos^2 = 1
sin x = - 1/2
x = - 30 or 330 deg . . . . and . . . x = 210 deg

2007-09-26 12:10:44 · answer #1 · answered by CPUcate 6 · 0 0

y = (cos x)/(2 + sin x)
y' = [(2+sinx)(-sinx) -(cosx)(cosx)]/(2+sinx)^2
y' = [-2sinx -sin^2x-cos^2x}/(2+sinx)^2
y' = (-2sinx -1)/(2+sinx)^2
Set y' =0 and solve for x getting
sinx = -1/2 --> x = -.5235987756 radians = 330 degrees or
210 degrees = 5pi/3 or 11pi/6 radians.
So tangent line is horizontal at 11pi/6 and 5pi/3 and all angles coterminal with these angles.

2007-09-26 19:29:31 · answer #2 · answered by ironduke8159 7 · 0 0

fedest.com, questions and answers